(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study contributes to knowledge of medicinal trees of Hazaribag district, Jharkhand, India. The goal of the research of medicinal trees was to learn more about the folklore around plant remedies. The majority of the territory is rich in plant diversity, and the residents of the economically disadvantaged villages of Hazaribag district primarily rely on agriculture and wild resources to meet their daily requirements. This document includes a list of 48 medicinal trees from 23 families and 41 genera. The botanical names, vernacular names, their respective family names, part of the plant used and their uses are indicated. Fabaceae was the dominant family followed by Moraceae, Meliaceae, Apocynaceae, Combretaceae, Euphorbiaceae, Myrtaceae, Rutaceae, Verbenaceae, Anacardiaceae, Annonaceae, Bignoniaceae, Boraginaceae, Lauraceae, Lythraceae, Moringaceae, Musaceae, Oleaceae, Rhamnaceae, Rubiaceae, Salicaceae, Sapotaceae, and Tiliaceae. The observations are based on local folklore and interview of various communities and tribes of the Hazaribag district. Therefore, the ethnobotanical knowledge of people and listing of plants of particular region are important tools that help in understanding human environment interactions.